How does the institutional environment improve the entrepreneurial quality of returnees? A configuration analysis based on a complex system view - Yiyang Shen; Hongtao Yang; Qiuhua Zhu (PLoS ONE, 2025)
Enhancing high-quality entrepreneurship among returnees stands as a pivotal mechanism in driving the robust economic development of emerging economies. The inquiry into crafting an enabling institutional framework to bolster the excellence of returnee entrepreneurship has garnered significant interest within academia and pertinent industries. Existing research primarily explores the impact of single institutional elements on returnee entrepreneurship, overlooking the diverse pathways to improve its quality under institutional complexity. Building on these insights, the current study explores the complex relationship between institutional configurations and the quality of returnee entrepreneurship in China. It also employs Necessary Condition Analysis (NCA) and dynamic Qualitative Comparative Analysis (QCA) methods based on a complex systems perspective. The research samples include 30 provinces in China. The findings reveal that while individual institutional factors do not, on their own, drive high-quality entrepreneurship among returnees in Periods 1 and 2, the importance of market environment and digital infrastructure becomes pronounced by Period 3. In the initial period, resource-driven entrepreneurship paired with emerging opportunities fosters high-quality outcomes. By Period 2, two additional configurations take shape: legitimacy-driven entrepreneurship under opportunity emergence and a dual-driver model that integrates both opportunities and resources. This dual-driver approach remains the dominant pathway for returnees in Period 3. Additionally, the market environment remains a critical factor across all periods. Digital infrastructure has become increasingly crucial for returnee entrepreneurship. Initially, the market environment focused primarily on financial services, but its connection with digital infrastructure intensified over time. In that regard, differences in economic resources and development across provinces have also led to region-specific pathways for improving the quality of returnee entrepreneurship. The findings contribute to a nuanced comprehension of the disparate progress of returnee entrepreneurial endeavors across regions within emerging economies. Most importantly, they offer theoretical insights to enhance the institutional framework in diverse regions, fostering the attainment of high-quality returnee entrepreneurship.